The NUBASE2020 evaluation of nuclear physics properties *This work has been undertaken with the endorsement of the IUPAP Commission on Symbols, Units, Nomenclature, Atomic Masses and Fundamental Constants (C2). (March 2021) - Kondev, F.G.; Wang 王, M. 猛; Huang 黄, W.J. 文嘉; Naimi, S.; Audi 欧, G. 乔治
Abstract: The NUBASE2020 evaluation contains the recommended values of the main nuclear physics properties for all nuclei in their ground and excited, isomeric (T1/2 100 ns) states. It encompasses all experimental data published in primary (journal articles) and secondary (mainly laboratory reports and conference proceedings) references, together with the corresponding bibliographical information. In cases where no experimental data were available for a particular nuclide, trends in the behavior of specific properties in neighboring nuclei were examined and estimated values are proposed. Evaluation procedures and policies that were used during the development of this evaluated nuclear data library are presented, together with a detailed table of recommended values and their uncertainties.